Exploring emergency action plans adoption in curbing crisis situations in secondary schools in Kagera, Tanzania - Challe, Getruda; Mislay, Moshi; Boniface, Raymond M. (Papers in Education and Development, 2024)
This study explored the adoption of Emergency Action Plans (EAPs) to manage crises in secondary schools within the Kagera Region. Employing a multiple case study design, the research involved 48 participants, with data collected through interviews, documentary reviews, and observations. Thematic analysis was used to interpret the data. Findings revealed that secondary schools lacked well-defined and comprehensive EAPs to address emergencies effectively. The adoption of EAPs was limited due to inadequate safety facilities, insufficient infrastructure, financial constraints, the absence of school nurses, and a general lack of knowledge regarding EAP implementation. The study concludes that ensuring a safe teaching and learning environment requires not just planning but the effective adoption and implementation of EAP to adequately prevent, mitigate, and respond to emergencies.